2009
DOI: 10.1063/1.3207748
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial investigation of (Ti1−xNbx)2AlC

Abstract: We have synthesized thin films of (Ti1−xNbx)2AlC by combinatorial method on TiC (111) seed layers grown on c-axis sapphire (Al2O3) substrates at 900 °C using magnetron sputter. X-ray diffraction showed the films to be c-axis oriented and epitaxial, and films contained a minor secondary phase of (Ti,Nb)C, irrespective of stoichiometry. Most notably, Raman spectroscopy suggest a sizable increase in the elastic modulus in the Nb-rich region as compared to either of the end members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, in light of the difficulty in synthesizing the MAX-nitrides by reactive sputtering, as well as the relative ease with which the MAX carbides can be grown by other sputtering techniques, there has been very little interest in employing reactive sputtering for synthesis of MAX carbides. Only a few unpublished attempts [108] have been made.…”
Section: Reactive Sputteringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in light of the difficulty in synthesizing the MAX-nitrides by reactive sputtering, as well as the relative ease with which the MAX carbides can be grown by other sputtering techniques, there has been very little interest in employing reactive sputtering for synthesis of MAX carbides. Only a few unpublished attempts [108] have been made.…”
Section: Reactive Sputteringmentioning
confidence: 99%
“…However, Ti is much more prone to resputtering by Ar than W; resulting in Ti-deficient films [131,132]. For MAX phases containing heavy M and/or A elements, resputtering by inert gas neutrals may be relevant and could possibly explain why some initial attempts [108,133] at synthesizing Ta-Al-C MAX-phase thin films were not successful, despite the fact that Ta 2 AlC, Ta 3 AlC 2 , and Ta 4 AlC 3 all exist in bulk form (see section…”
mentioning
confidence: 99%
“…2 Among the relatively few studies that exist on MAX-phase solid solutions in thin films, Scabarozi et al reported M-site solid solutions of (Ti,Nb) 2 AlC thin films. 17 From Raman scattering, they indirectly determined the elastic modulus, suggesting solid solution hardening. Furthermore, in thin films, the oxycarbide X-site solid solution Ti 2 Al(C,O) has been reported as a result of the incorporation of oxygen from the residual gas in a vacuum deposition process 18 or due to a reaction between TiC or Ti 2 AlC layers with an Al 2 O 3 substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other MAX phase materials have been deposited using magnetron sputtering [7][8][9][10][11][12][13][14] including Cr 2 AlC [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%